How Medicaid Accountable Care Organizations Advance Maternal Health Care Quality: Drivers of Change and Challenges From the Perspective of ACO Leaders, Clinicians, and Care Coordinators - SHANNON N. OGDEN; STEPHANIE LOO; MEGAN B. COLE; KATHRYN D. THOMPSON; KENNETH N. LIM; SARAH H. GORDON; COLLETTE N. NCUBE; ELIZABETH W. PATTON; KAREN E. LASSER; LOIS MCCLOSKEY (The Milbank Quarterly, 2026)
Policy Points Medicaid Accountable Care Organization contracts that include maternal health metrics can act as an important lever to prioritize and improve maternal health care quality and equity within health care systems. Medicaid Accountable Care Organizations should implement specialized maternal health programs to support metric achievement and provide dedicated resources to meaningfully affect maternal health care quality and equity. Context In the wake of a US maternal health crisis, Accountable Care Organizations (ACOs) may be a key opportunity to improve maternal health care. In 2018, Massachusetts Medicaid launched its ACO program through an 1115 waiver, which renewed and expanded in 2023. During the second waiver period, the ACOs expanded their emphasis on maternal health. However, there is limited understanding of how maternal health fits into Medicaid ACO strategic priorities, how ACOs implement maternal health initiatives, and the challenges they face. This study uses qualitative interviews with ACO leaders, clinicians, and care coordinators to explore how ACOs addressed maternal health care quality, while identifying key drivers of and challenges for change in maternal health care delivery across Massachusetts’ two waiver periods. Methods We conducted 23 semistructed interviews with 26 ACO leaders, clinicians, and care coordinators representing six of 17 Massachusetts Medicaid ACOs between September 2023 and December 2024. We analyzed professionally transcribed interviews using thematic analysis. Findings We identified three major themes: (1) Mandated ACO metrics drive maternal health priorities and practices, yet meeting metrics is challenging; (2) Shifts in Medicaid ACO priorities prompt the adaptation of existing programs or development of new initiatives to address maternal health; and (3) Health‐related social needs initiatives within the ACO are viewed as critical to maternal health care. The themes emphasized how Medicaid ACOs and health care systems adapted their programming in response to state‐level mandates to improve maternal health care quality. Conclusions Findings highlight the importance of aligning the design of Medicaid ACO programs with robust infrastructure and resources to support sustainable improvements in maternal health. Massachusetts’ Medicaid program achieved success in improving maternal care quality when it intentionally and strategically incorporated maternal health‐specific provisions into Medicaid ACO contracts.